Non-isothermal ionic mass transfer at vertical parallel plate electrodes under natural convection : Comparison and validity range of dimensionless correlations - Pasquale, Miguel Ángel (2002)
For non-isothermal ionic mass transport-controlled electrochemical reactions on vertical parallel plate electrodes under steady state natural convection, the dimensionless correlation Sh=0.9 (ScGr*)1/4, Sh, Sc and Gr* being Sherwood, Schmidt and Grashof number, respectively, earlier proposed (Electrochim. Acta 13 (1968) 1657; 14 (1969) 741), was extended covering almost two decades of (ScGr*)1/4. Data from different test reactions in the range −10≤ΔT′≤15 °C, utilising cells of similar geometry and cathode height in the range 0.025≤X≤1 cm were considered. Using the above correlation as reference, other dimensionless correlations later derived, considering data from the same test reactions and using electrochemical cells of approximately the same design, were critically reviewed. The validity range of these correlations covered a smaller range of (ScGr*)1/4 than the reference correlation, and their differences were explained in terms of cell designs and operating conditions.